2010
DOI: 10.1038/jp.2009.195
|View full text |Cite
|
Sign up to set email alerts
|

Documenting the NICU design dilemma: parent and staff perceptions of open ward versus single family room units

Abstract: Objective:With neonatal intensive care units (NICUs) evolving from multipatient wards toward family-friendly, single-family room units, the study objective was to compare satisfaction levels of families and health-care staff across these differing NICU facility designs.Study Design:This prospective study documented, by means of institutional review board-approved questionnaire survey protocols, the perceptions of parents and staff from two contrasting NICU environments.Result:Findings showed that demographic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
119
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(123 citation statements)
references
References 9 publications
3
119
0
1
Order By: Relevance
“…Research conducted to date concerning the impact of SFR NICUs has focused on the responses of the caregivers [21][22][23][24] while others have compared the perceptions of caregivers and parents. 25,26 When comparing differences between multibed and SFR NICUs, staff perceived that working in SFR NICUs resulted in higher job satisfaction and workplace quality and decreased stress. [21][22][23]26 However, many studies also found staff concerns related to adequacy of patient attention 25 and communication and isolation of staff [22][23][24] when working in SPR NICUs.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Research conducted to date concerning the impact of SFR NICUs has focused on the responses of the caregivers [21][22][23][24] while others have compared the perceptions of caregivers and parents. 25,26 When comparing differences between multibed and SFR NICUs, staff perceived that working in SFR NICUs resulted in higher job satisfaction and workplace quality and decreased stress. [21][22][23]26 However, many studies also found staff concerns related to adequacy of patient attention 25 and communication and isolation of staff [22][23][24] when working in SPR NICUs.…”
mentioning
confidence: 98%
“…25,26 When comparing differences between multibed and SFR NICUs, staff perceived that working in SFR NICUs resulted in higher job satisfaction and workplace quality and decreased stress. [21][22][23]26 However, many studies also found staff concerns related to adequacy of patient attention 25 and communication and isolation of staff [22][23][24] when working in SPR NICUs. Staff perceived that parents were afforded greater privacy in SFR 21,22,26 and this was consistent with the perceptions of parents that SFR afforded better privacy for bonding and breastfeeding 25 and overall privacy.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Caregivers, too, recognize that an SFR design improves the sensory environment for newborns and is more desirable for families, but creates communication and collaboration impediments for both families and staff that are not found in open, multi-bed rooms. [3][4][5] In this issue, two studies using historical controls of multi-bed NICUs showed that moving to a new SFR NICU may improve staff perception of workplace quality (Stevens et al 6 ), but this is dependent to some degree on the type of caregiver and the length of time after the move during which the caregivers are surveyed (Domanico et al 7 ). Furthermore, the Domanico study showed that caregiver concerns must be considered subjective, as the perception that the safety of the infant might be compromised in the SFR could not be confirmed by increases in mortality or length of stay.…”
Section: Gustave Le Bonmentioning
confidence: 99%
“…The impact on breastfeeding continuation at 4 weeks was highlighted by a recent study showing that mothers of term NICU-admitted infants were less likely to continue breastfeeding than mothers of nonadmitted infants even after adjusting for the confounding variables of race, maternal age, maternal education, mode of delivery, and Medicaid status. 35 Some of the adverse consequences of NICU admission may be ameliorated in nurseries with single family room patient care spaces 36,37 ; however, NICU admission remains an important outcome measure when considering VBAC versus ERCD and should be explored further.…”
Section: Areas For Future Researchmentioning
confidence: 98%